Igbo Folktales and the Evolution of the Idea of Chukwu as the Supreme God of Igbo Religion - Azuonye, Chukwuma (Nsukka Journal of Linguistics and African Languages, 1987)
Semantic Scholar extracted view of "Igbo Folktales and the Evolution of the Idea of Chukwu as the Supreme God of Igbo Religion" by Chukwuma Azuonye
free